(untitled) (Вестник КазНУ. Серия Востоковедения, 2016)
В этой статье рассматривается вопросы изучения тюркизмов в славянских языках, пути проникновения, проблемы взаимовлияния и взаимообогащения контак- тирования языков. In this article it is considered studying questions of Turkic words in slavic languages, a way of penetration, a problem of mutual influence and mutual enrichment of engagement of languages.